Development of communication skills in english through supplementary materials for health technicians: an experimental study in hygiene and epidemiology - Cruz-Camacho, Lisvette (2025)
English proficiency in health care is crucial for access to scientific information and international collaboration. This study evaluated the impact of complementary materials (audios, interactive videos, technical guides and simulations) on the development of communication skills in English in 12 second year students of Hygiene and Epidemiology in the Faculty of Technology-Nursing, Villa Clara, Cuba, during 2024-2025. A quasi-experimental design with pre-test and post-test was implemented, combining quantitative (language competence evaluations) and qualitative methods (survey and participant observation) methods. The results after the intervention were superior in the quantitative order, for example, in the oral test the progress from A2 to B1 was 75% of the students. Likewise, in the written test, 92% reached B1 level, 87% were correct in terminology, 83% in case analysis and 79% in professional writing. Among the qualitative results, the unanimous perception of professional usefulness, increased autonomy, integration of knowledge and positive evaluation of the materials stand out. It is concluded that the integration of supplementary materials adapted to the healthcare context optimizes the learning of technical English in healthcare students.